The impact of a decade of digital transformation on employment, wages, and inequality in the EU: A "conveyor belt" hypothesis - Matteo Richiardi; Leonie Westhoff; Caterina Astarita; Ekkehard Ernst; Clare Fenwick; Neysan Khabirpour; Lorenzo Pelizzari (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2024)
We study the effects of digital transformation in the EU on individual employment outcomes, wage growth, and income inequality, during the decade 2010-2019. Our results allow us to formulate a "conveyor-belt" hypothesis, whereas digital skills are important for finding a job, but less so for retaining it. The ability of out-of-work individuals with higher digital skills to jump back on the labour market is reduced for those with higher education, suggesting a faster depreciation of their digital skills. A similar effect, although of limited size, is found for earning growth: out-of-work individuals with higher digital skills are not only more likely to find a job, but experience higher earning growth, compared to their peers with lower digital skills. Our results point to a vulnerability of workers "left behind" from the digital transformation and the labour market. The overall effects on inequality are, however, limited.
Keywords: J24; J31; D31; 330; Digital transformation; digital skills; inequality; employment; wages; EU